Appendix 5.7: Project Completion Report: Philippine National Railways - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies; Vol 27, No 1-2-Vol 28, No 1-2 (2012-2013): Marcos Pa Rin! The Legacy and the Curse of the Marcos Regime, 2017)
Unexplored in the literature on Marcos supporters is the apparent overlap between many Philippine railway workers and enthusiasts and Marcos loyalists. This can be linked to a perception that Marcos had done more for railway transportation in the country than any postSecond World War president before him. After all, it was during his regime that the first line of the country’s light railway transit (LRT) system was built (on the back of enormous foreign loans, of course). However, this excerpt from a project completion report, requested from the Asian Development Bank, shows that the PNR’s decline started well within the Marcos regime, probably not coincidentally while another railway project, the LRT, was being built.